Ten years of animal production and range research in Botswana - Ministry of Agriculture, Botswana (1980)
Reports results of investigations carried out in Botswana on range management. Topical discussions on bush control, grazing systems, stocking rates, range improvement through the introduction of fodder species, agronomy, range monitoring and range ecology included. Additional information on animal production, particularly on the supplementation of breeding cows, feeding potentials of crop residues, dietary selection and grazing habits of goats, reproductive physiology and breed comparison of beef cattle, milking systems, sheep and goat husbandry, and economic evaluation of animal production systems included.